Understanding AL amyloidosis with a little help from in vivo models - Martinez-Rivas, Gemma; Bender, Sébastien; Sirac, Christophe (Frontiers in Immunology, 2022)
Monoclonal immunoglobulin (Ig) light chain amyloidosis (AL) is a rare but severe disease that may occur when a B or plasma cell clone secretes an excess of free Ig light chains (LC). Some of those LC tend to aggregate into organized fibrils with a β-sheet structure, the so-called amyloid fibrils, and deposit into the extracellular compartment of organs, such as the heart or kidneys, causing their dysfunction. Recent findings have confirmed that the core of the amyloid fibrils is constituted by the variable (V) domain of the LC, but the mechanisms underlying the unfolding and aggregation of this fragment and its deposition are still unclear. Moreover, besides the mechanical constraints exerted by the massive accumulation of amyloid fibrils into organs, the direct toxicity of these variable domain LC, full-length light chains or primary amyloid precursors (oligomers) seems to play a role in the pathogenesis of the disease. Many in vitro studies have focused on these topics, but the variability of this disease, in which each LC presents unique properties, and the extent and complexity of affected organs, makes its study in vivo very difficult. Accordingly, several groups have been focused on the development of animal models for years, with some encouraging but mostly disappointing results. In this review, we aimed to discuss about the experimental models that have been used to better understand the unknowns of this pathology with an emphasis on in vivo approaches. We will also focus on why reliable AL amyloidosis animal models remain so difficult to obtain and what does this tell us about the pathophysiology of the disease.